1999
DOI: 10.1016/s0092-8674(00)81519-6
|View full text |Cite
|
Sign up to set email alerts
|

Cdk Phosphorylation Triggers Sequential Intramolecular Interactions that Progressively Block Rb Functions as Cells Move through G1

Abstract: We present evidence that phosphorylation of the C-terminal region of Rb by Cdk4/6 initiates successive intramolecular interactions between the C-terminal region and the central pocket. The initial interaction displaces histone deacetylase from the pocket, blocking active transcriptional repression by Rb. This facilitates a second interaction that leads to phosphorylation of the pocket by Cdk2 and disruption of pocket structure. These intramolecular interactions provide a molecular basis for sequential phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
732
1
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(786 citation statements)
references
References 46 publications
35
732
1
13
Order By: Relevance
“…A dual action of E1A involving: (1) association with E2F-Rb complexes via the LxCxE motif, preventing binding of HDAC; and (2) release of free E2F through the action of CR1 (and possibly the GFP motif) would be analogous to the proposed roles of cyclin/CDK complexes in Rb inactivation (Harbour et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A dual action of E1A involving: (1) association with E2F-Rb complexes via the LxCxE motif, preventing binding of HDAC; and (2) release of free E2F through the action of CR1 (and possibly the GFP motif) would be analogous to the proposed roles of cyclin/CDK complexes in Rb inactivation (Harbour et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In its active state, RB inhibits cell cycle progression through its ability to repress transactivation of genes required for DNA replication and G2/M progression (reviewed in Sherr and McCormick, 2002;Cam and Dynlacht, 2003;Cobrinik, 2005). Activated CDK4/cyclin D1 complexes initiate phosphorylation of RB in response to mitogens (Mittnacht, 1998;Harbour et al, 1999). This phosphorylation event disrupts the ability of RB to mediate transcriptional repression and therefore nullifies its antiproliferative function (Hinds et al, 1992;Dowdy et al, 1993;Ewen et al, 1993;Harbour et al, 1999).…”
Section: Cyclin D1 and Cell Cycle Controlmentioning
confidence: 99%
“…Activated CDK4/cyclin D1 complexes initiate phosphorylation of RB in response to mitogens (Mittnacht, 1998;Harbour et al, 1999). This phosphorylation event disrupts the ability of RB to mediate transcriptional repression and therefore nullifies its antiproliferative function (Hinds et al, 1992;Dowdy et al, 1993;Ewen et al, 1993;Harbour et al, 1999). Early evidence suggested that the ability of cyclin D1 to promote RB phosphorylation is crucial for its cell cycle function, as cancer cells that are defective in RB are refractory to cyclin D1 action (Lukas et al, 1994a(Lukas et al, , 1995a).…”
Section: Cyclin D1 and Cell Cycle Controlmentioning
confidence: 99%
“…The conformational changes that occur as a result of early phosphorylation events on pRb collectively lead to the interaction of pRb with cyclin E/Cdk2, which phosphorylates S567. As S567 is located in the core of the pocket region, phosphorylation of this residue prevents pRb from binding to and inactivating E2F-1 (Harbour et al, 1999).…”
Section: Introductionmentioning
confidence: 99%